TGF-β1-triggered BMI1 and SMAD2 cooperatively regulate miR-191 to modulate bone formation - Xiao-Fei Zhang; Zi-Xuan Wang; Bo-Wen Zhang; Kun-Peng Huang; Tian-Xing Ren; Ting Wang; Xing Cheng; Ping Hu; Wei-Hua Xu; Jin Li; Jin-Xiang Zhang; Hui Wang (Elsevier, 2024)
Transforming growth factor β 1 (TGF-β1), as the most abundant signaling molecule in bone matrix, is essential for bone homeostasis. However, the signaling transduction of TGF-β1 in the bone-forming microenvironment remains unknown. Here, we showed that microRNA-191 (miR-191) was downregulated during osteogenesis and further decreased by osteo-favoring TGF-β1 in bone marrow mesenchymal stem cells (BMSCs). MiR-191 was lower in bone tissues from children than in those from middle-aged individuals and it was negatively correlated with collagen type I alpha 1 chain (COL1A1). MiR-191 depletion significantly increased osteogenesis and bone formation in vivo. Hydrogels embedded with miR-191-low BMSCs displayed a powerful bone repair effect. Mechanistically, transcription factors BMI1 and SMAD2 coordinately controlled miR-191 level. In detail, BMI1 and pSMAD2 were both upregulated by TGF-β1 under osteogenic condition. SMAD2 activated miR-191 transcription, while BMI1 competed with SMAD2 for binding to miR-191 promoter region, thus disturbing the activation of SMAD2 on miR-191 and reducing miR-191 level. Altogether, our findings reveal that miR-191 regulated by TGF-β1-induced BMI1 and SMAD2 negatively modulated bone formation and regeneration, and inhibition of miR-191 might be therapeutically useful to enhance bone repair in clinic.